Adhesion evaluation of dental ceramics sintered on novel titanium alloys - Stefan Tudoran; Lucian Toma Ciocan; Bogdan Mihai Galbinasu; Ion Patrascu; Vlad Gabriel Vasilescu (Amaltea Medical Publishing House, 2023)
Metal-ceramics dental prosthetic restorations are clinically recommended for their advantages related to good esthetic features along with strength and long-term clinical use. Given the importance of the quality of the metalceramic (M-C) bond, the metal substructure analysis has a major importance to the quality of the manufactured dental prosthesis. In the present study was analyzed the behavior of experimentally developed novel titanium alloys (TiZr, TiZrNbTa) comparatively with other frequently used titanium alloys (e.g., Ti Cp, Ti6Al4V) designated for the technology of mixed prosthetic restorations. All samples were been plated, simultaneously in the same conditions, with the same titanium specific compatible ceramic plating material (Ti22 Noritake). The examination of the surface of both components was performed by scanning electron microscopy SEM) analysis and EDS analysis, which showed differences in the characteristics of the oxide layer formed, depending on the composition of the metal substructure. The evaluation of the alloy-ceramic adhesion was performed by mechanical tests, which attest to the fact that the adhesion and the quality of the bond between metal and ceramic depend on the thickness of the oxide films formed. The results showed the superiority of titanium novel titanium alloys (TiZr, TiZrNbTa), having highest hardness values, highest values of shear strength, a continuous thin oxide films, and consequently, a better metal-ceramic adhesion. Comparatively, less ductile titanium alloys (TiZrNbTa/Ti3) are generating lower adhesion forces with values above 30MPa in some samples justifying less predictable clinical results.